2016
DOI: 10.5194/acp-16-8749-2016
|View full text |Cite
|
Sign up to set email alerts
|

Variability of mineral dust deposition in the western Mediterranean basin and south-east of France

Abstract: Abstract. Previous studies have provided some insight into the Saharan dust deposition at a few specific locations from observations over long time periods or intensive field campaigns. However, no assessment of the dust deposition temporal variability in connection with its regional spatial distribution has been achieved so far from network observations over more than 1 year. To investigate dust deposition dynamics at the regional scale, five automatic deposition collectors named CARAGA (Collecteur Automatiqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 76 publications
(96 reference statements)
19
73
0
1
Order By: Relevance
“…Rinse water and rainwater pass through an AA Millipore ® cellulose ester filter with a 0.8 µm porosity in order to collect the insoluble fraction of the deposition. A complete description of the CARAGA collector and sampling network can be found in Laurent et al (2015) and Vincent et al (2016). After being brought back to the laboratory, collected filters were ashed following a progressive increase in temperature up to 550 • C in order to destroy and vaporize the filter and organic matters.…”
Section: Sampling Of Insoluble Deposition and Total Mass Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rinse water and rainwater pass through an AA Millipore ® cellulose ester filter with a 0.8 µm porosity in order to collect the insoluble fraction of the deposition. A complete description of the CARAGA collector and sampling network can be found in Laurent et al (2015) and Vincent et al (2016). After being brought back to the laboratory, collected filters were ashed following a progressive increase in temperature up to 550 • C in order to destroy and vaporize the filter and organic matters.…”
Section: Sampling Of Insoluble Deposition and Total Mass Measurementsmentioning
confidence: 99%
“…From 2011 to 2013, 108 samples corresponding to the most intense weekly dust deposition samples were studied by Vincent et al (2016), and a Saharan origin was identified for 107 selected samples by using satellite data and air mass trajectories. The selected samples account for 84, 78 and 73 % in mass of the total deposition in Lampedusa (37 samples), Mallorca (21 samples) and Corsica (11 samples), and it contributes for around 50 % in Frioul (21 samples) and Le Casset (17 samples).…”
Section: Sampling Of Insoluble Deposition and Total Mass Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Buat-Ménard and Chesselet, 1979;Martin et al, 1991;Swap et al, 1992;Duce, 1995;Alpert et al, 1998;Mahowald et al, 2009Mahowald et al, , 2011Maher et al, 2010;Liu et al, 2011;Choobari et al, 2014;Li et al, 2016). Desert dust aerosol is of particular interest in the Mediterranean region where it is (i) frequently observed in high concentrations in the troposphere; (ii) is a major component of surface PM 10 Rea et al, 2015), aerosol optical depth (Moulin et al, 1998;Gkikkas et al, 2013;Nabat et al, 2013), atmospheric deposition (Pye, 1992;Vincent et al, 2016); and (iii) affecting the regional air quality (Querol et al, 2009); atmospheric thermodynamics (e.g. Alpert et al, 1998;Chaboureau et al, 2011); radiative budget and climate (e.g.…”
Section: Introductionmentioning
confidence: 99%